Pre-industrial and future shifts in seasonal precipitation climatology for large river basins across the continental U.S.A - Kyungmin Sung; James H Stagge (Environmental Research Communications)
This study investigates seasonal precipitation trends across major watersheds in the continental United States over the past millennium (850 CE) and into the projected future (2100 CE). Using a non-stationary Standardized Precipitation Index (SPI) model, we quantify shifts in median precipitation climatology relative to an 1850 pre-Industrial baseline, integrating modern observations, tree-ring reconstructions, and climate model simulations. Trends at a gridded scale were then summarized by HUC-2 watershed to produce relevant results for water resources planning. Results show that northern and eastern watersheds have experienced wetting trends in the modern, Industrial era (post 1850), while southwestern regions have undergone intensifying drying trends, particularly during the summer. Trends vary seasonally, the most distinct north-south division occurring in winter and spring, while the region of increased drying expands to cover most of the U.S. during the summer. These trends are projected to continue on their current trajectory through the end of the century. By placing modern and projected precipitation trends into a multi-century historical context, we show that the magnitude of modern trends has exceeded pre-Industrial variability in many watersheds, suggesting the role of anthropogenic climate change in precipitation shifts. This study emphasizes the importance of adapting water management systems to ensure sustainable water availability under evolving climatic conditions. For example, the findings can inform water resources managers when reassessing water infrastructure and operations to mitigate the potential of increased flood risks in wetting regions and heightened water scarcity in drying areas.